PERKEMBANGAN POPULASI HAMA (Ephestia cautella) PADA BEBERAPA VARIETAS BAWANG PUTIH (Allium sativumL.) DI GUDANG PENYIMPANAN KECAMATAN SEMBALUN - ahna1 ahna2 (CROP AGRO, Scientific Journal of Agronomy, 2020)
The development of garlic from 2012-2016 in NTB Province has reached an average of Erplae Tele Sutetle Sue Em Emphass Font Selet Paragrapn Syen tang The development of garlic from 2012-2016 in NTB Province has reached an average. which is 7.929-11.001 tons / ha. But in its development did not escape the interference of plant-disturbing organisms (OPT) such as the pest Ephestia cautella. The purpose of this study was to determine the development of the Ephestia cautella pest in several varieties of garlic in the Sembalun District Storage Warehouse. The method used in this research is descriptive method with survey techniques and data collection in the field at the farmer's warehouse in Sembalun District, East Lombok Regency, West Nusa Tenggara. The results of the study found that the egg population in sanggah varieties was an average of 31.21, the average larval population was 2.15 and the average moth population was 1.70. The intensity of attacks with an average of 10.02% and an average population development of 29.85 tails. Based on the results of the study it is suggested that further research is needed on controlling egg populations using plant, biological, chemical, and mechanical controls. S WORDS